Aerogels of graphene oxide - clay nanocomposite as reusable and highly selective absorbent - Lim, Kramer Joseph A. (College of Engineering, University of the Philippines Diliman, 2014)
Occurrence of environment pollution due to oil spills have created a great need to find more efficient materials for cleanup operations. Absorption, a physical means, has been deemed the most effective approach for being economically sound, efficient and readily available. This research highlights the use grahene oxide (GO), montmorillonite (MMT) and poly (vinyl alcohol) PVA as precursors to synthesize a novel polymeric aerogel as absorbent for oil spill cleanup.It is interesting to note that the aerogels manifested hydrophobicity even though its individual constituents are hydrophilic in nature.Silanization further enhanced the aerogel's hydropocity oleophilicity and promoted mechanical resilience.With an absorption capacity of up to 23 times it initial weight, high selectivity to oil and organic solvents,mechanical robustness reusability and low density, the engineered aerogel is a promising absorbent material for oil- water separation.